Establishment of student's character through writing religious poetry learning by using type cooperative method think pair share (TPS) - Liesna Andriany (Proceedings of AICS - Social Sciences, 2013)
Character education can be said as a process for improving human personality. In other words it is a human effort to establish themselves as a noble man.It is the fruit of a process of internalization of core values or positive values. Quality character education can be obtained in the teaching of literature through writing religious poetry with learning strategies TPS type. Character will appear and grow in student intelligence reflected in cognition, emotion and culture.Keywords: Student’s Character, Reiligious Poetry, Coorperative Method